Gestão da qualidade aplicada a implantação de tecnologia LED na iluminação pública - CARNEIRO, André Luis Costa (2018)
Energy efficiency is one of the most discussed topics when talking about sustainability. The world population has grown rapidly in recent years and consequently energy consumption. Therefore, the use of more efficient technologies arises in order to reduce global energy demand and avoid the construction of new plants, reducing the consumption of natural resources and pollution. Regarding the application of energy efficiency in public lighting (PL), the focus of this work, the use of Light Emitting Diode (LED) technology is more present today, as a way to reduce the consumption of electric energy in cities and increase the life quality of the population, with regard to aspects of illumination. However, because it is a new technology, not yet matured for applications in external areas and subject to inclement weather, several problems still need to be studied and solved. This work proposes a methodology for managing the operation and maintenance of PL, with real cases occurring in Brazilian cities and a real case study in the implementation of LED technology in public lighting in the city of São José de Ribamar - MA.